Control of MAIT cell functions by cytokines in health and disease - Camard, Laetitia; Bianchi, Elisabetta; Rogge, Lars (Frontiers in Immunology, 2025)
Mucosal-associated invariant T (MAIT) cells are innate-like T cells that express a semi-invariant T cell receptor (TCR). These cells predominantly reside in tissues, such as the liver, lung, skin and the gastrointestinal tract. MAIT cells can be activated via their TCR that recognizes riboflavin metabolites presented by the MHC class I-related protein 1 (MR1). These cells can also be activated in a TCR-independent manner by cytokines, in particular IL-12 and IL-18, but also by type I interferons, IL-7, IL-15 and IL-23, underlining their innate-like characteristics. MAIT cells have important functions in antibacterial and viral immunity but also in tissue repair and homeostasis. Recent studies highlighted the plasticity of MAIT cells in response to cytokines, suggesting an important role of the cytokine milieu in modulating MAIT cell functions. Here, we discuss how cytokines control MAIT cell functions in various contexts.